The Effect Of Ie-Cepa, Gross Domestic Product, And Exchange Rate On Indonesia’s Exports To Efta - Dewi, Ida Ayu Putu Widyastari; Widanta, Anak Agung Bagus Putu (LPPM-STPI, 2023)
The Indonesia-European Free Trade Association Comprehensive Economic Partnership deal (IE-CEPA) is a proposed deal that links Indonesia's market access to EFTA, capacity building, and trade and investment facilitation. The goal of this research was to examine the impact of the IE-CEPA policy, GDP, and exchange rate on Indonesian exports to EFTA nations (studies in Switzerland, Norway, and Iceland). The IE-CEPA policy, which is assumed to be a dummy variable in this analysis, GDP collected from Worldbank statistics, and the exchange rate received from the Bank Indonesia website from 2013 to 2022 are the independent variables used in this study. The value of Indonesia's exports to other nations is utilized as the dependent variable. EFTA destinations, namely Switzerland, Norway and Iceland obtained from the Central Statistics Agency (BPS) from 2013 to 2022. This study employs panel data and a Fixed Effect Model (FEM) computed using the E-Views tool. The value of R2 = 0.940413 indicates that the estimated model can explain 94.0413 percent of the connection between the dependent and independent variables, with the remaining 5.9587 percent explained outside the estimated model. The findings of this study show that the IE-CEPA policy has no significant impact on Indonesia's exports to EFTA countries, Gross Domestic Product (GDP) has a positive and significant impact on Indonesia's exports to EFTA countries, and the exchange rate has a positive and significant impact.